2019
DOI: 10.1093/nar/gkz266
|View full text |Cite
|
Sign up to set email alerts
|

The mitoribosome-specific protein mS38 is preferentially required for synthesis of cytochrome c oxidase subunits

Abstract: Message-specific translational regulation mechanisms shape the biogenesis of multimeric oxidative phosphorylation (OXPHOS) enzyme in mitochondria from the yeast Saccharomyces cerevisiae . These mechanisms, driven mainly by the action of mRNA-specific translational activators, help to coordinate synthesis of OXPHOS catalytic subunits by the mitoribosomes with both the import of their nucleus-encoded partners and their assembly to form the holocomplexes. However, little is known regarding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 46 publications
4
23
0
1
Order By: Relevance
“…bS22 conserved in actinobacteria located at the eL41 binding site 71 . Finally, in human and yeast mitochondria, the N-terminal part of the mitochondria-specific mS38 protein occupies this position [72][73][74] . mS38 is proposed to be related to translation of mitochondrial mRNAs lacking typical SD sequences 74 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…bS22 conserved in actinobacteria located at the eL41 binding site 71 . Finally, in human and yeast mitochondria, the N-terminal part of the mitochondria-specific mS38 protein occupies this position [72][73][74] . mS38 is proposed to be related to translation of mitochondrial mRNAs lacking typical SD sequences 74 .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in human and yeast mitochondria, the N-terminal part of the mitochondria-specific mS38 protein occupies this position [72][73][74] . mS38 is proposed to be related to translation of mitochondrial mRNAs lacking typical SD sequences 74 . Overall, the whole data indicate that variability of eL41 might be related to evolution of translation initiation.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, Arabidopsis mitoribosomes altered due to the silencing of the nuclear RPS10 gene encoding mitochondrial ribosomal protein S10 differentially translate two subsets of mRNAs, those encoding OXPHOS subunits and ribosomal proteins with, respectively, slightly lowered and clearly enhanced efficiency compared to the wild-type. A mitoribosome-mediated translation regulation has also been reported for yeast mitoribosome lacking the SSU protein mS38/Cox24 [51]. It was reported that mS38 is preferentially required for translation initiation of COX1, COX2 and COX3 mRNAs.…”
Section: Heterogeneity Of the Mitoribosome Compositionmentioning
confidence: 76%
“…mS38 protein, which is lacking in E. coli , although present (as an orthologous bS22) in some bacteria which have many leaderless mRNAs, is involved in formation of the channel accommodating mRNA part 5′ to the P-site. In yeast mitochondria this protein was demonstrated to selectively enhance translation of specific mitochondrial mRNAs [ 37 ]. A protein mS37, which is also uniquely found in mitoribosomes also contributes to the accommodation of mRNA 5′-region [ 38 ].…”
Section: Peculiar Features Of Mitochondrial Translation Apparatusmentioning
confidence: 99%
“…The protein mS39 binds the small subunit from the cytoplasmic side and facilitate a recruitment of mRNAs [ 39 , 40 ]. Proteins mS37 and mS38 are located in the platform region of the small subunit [ 96 ] and also contribute to the interaction with mRNAs [ 37 , 38 ]. The latter protein is nearest to the modification site.…”
Section: Common Modified Nucleotides In Mitochondrial and Bacteriamentioning
confidence: 99%